Signifikansi Pendidikan Spiritual, Mental, Inteligen, Skill (SMIS) Bagi Pendidikan Anak Usia Dini Sesuai Kerangka Pikir Teologi Reformed Di KB-TK Kristen Logos Bintaro - Sitohang, E. Maria Kristine; Tambunan, Aripin; Subeno, Sutjipto (Institut Agama Kristen Negeri Tarutung, 2024)
Early childhood education is a form of preschool education aimed at preparing young children for primary school. Currently, many early childhood education institutions (PAUD) have adopted curricula that not only focus on enhancing intellectual intelligence but also promote holistic education. The Christian Playgroup (KB) and Kindergarten (TK) LOGOS Bintaro are examples of PAUD institutions implementing this holistic educational concept by integrating Spiritual, Mental, Intellectual, and Skills (SMIS) aspects to prepare children for the next level of education.This research aims to explore the significance of the SMIS educational concept for early childhood, particularly the spiritual values as its foundational element, and to understand whether the meaning of this education is shared among students, parents, and educators. The research methodology uses a qualitative design with a phenomenological approach. The theory used to review SMIS education is based on the Reformed Theology framework. The results of this study indicate that the SMIS education applied at KB-TK Christian LOGOS Bintaro is significant in forming the spiritual, mental, and skills foundation for students, supporting holistic development through collaboration between the school, parents, and church, and guiding children to become Christian individuals ready to serve God and others. The SMIS educational concept aligns with the Reformed Theology framework.